SHM_415566_HST_3D Pottery Rim Fragment in the Pitted Ware Culture/Fagervik III Style - Lernestål, Erik; Myrin, Ola; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a Middle Neolithic pottery rim fragment in the Pitted Ware Culture/Fagervik III style collected from Fagervik in Östergötland and held in the collections of the National Historical Museums in Stockholm. The fragment shows a herringbone pattern of cord impressions as well as deeper impressions.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=668

Link to Sök I Samlingarna

https://samlingar.shm.se/object/AD48B67E-FBD2-497F-9B97-59251125D66A
Keywords: 3D Model; Museum Object; Archaeology; Archaeology; Photogrammetry; History and archaeology; Archaeology/history; Fagervik; Pitted Ware Culture; Swedish Middle Neolithic; Dynamic Collections; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi